Left ventricular ejection fraction adds value over the GRACE score in prediction of 6-month mortality after ACS: the MADDEC study - Terho Lehtimäki; Leo-Pekka Lyytikäinen; Kjell Nikus; Markku Eskola; Jussi Hernesniemi; Niku Oksala; Nina Syyli; Markus Hautamäki; Kari Antila; Shadi Mahdiani (Open Heart)
Background Reduced left ventricular ejection fraction (LVEF) is a risk marker for mortality after an acute coronary syndrome (ACS). Global Registry of Acute Coronary Events (GRACE) risk score, developed almost two decades ago, is the preferred scoring system for risk stratification in ACS. The aim of this study was to validate the GRACE score and evaluate whether LVEF has incremental predictive value over the GRACE in predicting 6-month mortality after ACS in a contemporary setting.Methods A retrospective analysis of all 1576 consecutive patients who were admitted to Tays Heart Hospital and underwent coronary angiography for a first episode of ACS (2015–2016). Clinical risk factors were extensively recorded. Adjusted Cox regression analysis was used to analyse the associations between LVEF and the GRACE score with 6-month all-cause mortality. The incremental predictive value was assessed by the change in C-statistic by Delong’s method for paired samples and by index of discrimination improvement (IDI).Results In univariable analysis, both LVEF and the GRACE were associated with 6-month mortality, and after applying both variables into the same model, the results remained significant (GRACE score: HR: 1.036, 95% CI 1.030 to 1.042; LVEF: HR: 0.965, 95% CI 0.948 to 0.982, both HRs corresponding to a one unit change in the exposure variable). The GRACE score demonstrated good discrimination for mortality (C-statistic: 0.833, 95% CI 0.795 to 0.871). Adding LVEF to the model with the GRACE score improved model performance significantly (C-statistic: 0.848, 95% CI 0.813 to 0.883, p=0.029 for the improvement and IDI 0.0171, 95% CI 0.0016 to 0.0327, p=0.031).Conclusions Adding LVEF to the GRACE score significantly improves risk prediction of 6-month mortality after ACS.